Characteristics of Corn Stover Components Pyrolysis at Low Temperature Based on Detergent Fibers - Wang, Fang; Zhang, Deli; Chen, Mei; Yi, Weiming; Wang, Lihong (Frontiers in Bioengineering and Biotechnology, 2019)
In order to study the effect of biomass components on the low temperature (30–400°C) pyrolysis, the thermogravimetric analysis (TGA) of corn stover (CS) and its three detergent fibers (extracted by Van Soest method) were studied, and the model compounds of cellulose, hemicellulose and lignin were also tested as comparison. The results shows the low temperature pyrolysis index (P) is significantly different (PADL < Plignin < PCS < PNDF−CS < Pxylan < PADF−CS < Pcellulose). Klason-lignin has stronger thermal stability and decomposes more difficult than alkali lignin. The original cross-linked structure and interaction of the three components inhibited volatiles releasing, especially significant below 300°C. The synergistic effect between cellulose and lignin promoted devolatilization and decreased the initial temperature of cellulose decomposition. At last, the low temperature pyrolysis kinetics parameters (apparent activation energy and pre-exponential factor) of CS and its detergent fibers were calculated via the Coats-Redfern methods. This study can provide a theoretical basis for optimization of process conditions and industrial application of low temperature pyrolysis for lignocellulosic biomass.